Enhancing Fish Farmers’ Income in Bekasi: Blue Economy and Digital Transformation with Penta Helix Support - Larasati, Ikramina; Amin, Grace; Retno, Hernawati; Amalina, Shinta; Aima, Havidz (President University, 2024)
This research explores the role of Indonesia's blue economy in promoting sustainable development and economic growth, focusing specifically on the catfish industry. With increasing domestic and export demand, the catfish sector is positioned to capitalize on the opportunities presented by marine-based activities, such as fisheries and aquaculture. To maximize this potential, stakeholders must adopt digital transformation and implement a collaborative Penta-Helix model, which integrates government, academia, industry, community, and media. This study examines critical success factors for catfish entrepreneurs, highlighting how the Penta-Helix model can facilitate digital innovation and enhance income levels. Mixed method was employed in this research. By leveraging technologies like the Internet of Things (IoT), catfish producers can improve operational efficiency, optimize resource management, and expand market reach. Real-time monitoring of essential production factors, including water quality and feed consumption, enables more efficient resource utilization, reduced production costs, and improved product quality. The findings indicate that the synergy between digital transformation and the Penta-Helix model is vital for enhancing the competitive edge of catfish enterprises and fostering sustainable economic growth in Indonesia.